Genetic variability, correlations and path coefficient analysis of components of seed yield in cowpea (Vigna unguiculata) - O. J., Ariyo (Universiti Putra Malaysia Press, 1995)
Twenty-six varieties of cowpea (Vigna unguiculata L Walp,) were evaluated in the field to study genetic variability, inter-character relationships as well as the path analysis oj components oj seed yield. Seed yield was the most variable character with genotypic coefficient of variation (gvc) and phenotypic coefficient of variation (pvc) of 22.1 I and 35.25%, respectively. Days to flowering was the least variable with gvc and pvc of 1.93 and 2.30%, respectively. Weight of 100 seeds had the highest heritability estimate of 92.33% while number of peduncles per plant exhibited the lawest heritability estimate of 30.11%. Number of peduncles per plant number of branches per plant and number of branches per peduncle showed signficant and positive phenotypic correlation with seed yield. Only number of peduncles per plant and number of branches per plant showed positive phenotypic correlation with seed yield. Path coefficient analysis revealed that seed yield was affected by weight of 100 seeds, number of seeds per pod, number of branches per plant and number of pods per peduncle.